2010
DOI: 10.1029/2010gl045310
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of the FeO orange bands in the terrestrial night airglow spectrum obtained with OSIRIS on the Odin spacecraft

Abstract: An unidentified pseudo‐continuum in the 600 nm region is observed in the upper mesosphere with the limb‐scanning OSIRIS imaging spectrograph on‐board the Odin spacecraft. Averages of low latitude spectra at a series of tangent limb altitudes from 75 to 105 km are assembled and matched with synthetic spectra of the known night airglow emission band systems to isolate the underlying airglow continuum. The upper limit of the NO + O → NO2* air afterglow continuum component in the observed 600 nm pseudo‐continuum i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 34 publications
3
36
0
Order By: Relevance
“…Very recently, Evans et al (2010) reported on the discovery of the orange bands of excited FeO in the low latitude nightglow spectrum. The excited FeO is the result of the reaction between Fe and O 3 and the wavelength region covered by the FeO emission is from ∼520 nm to longer than 700 nm, i.e.…”
Section: No From the Photometric Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Evans et al (2010) reported on the discovery of the orange bands of excited FeO in the low latitude nightglow spectrum. The excited FeO is the result of the reaction between Fe and O 3 and the wavelength region covered by the FeO emission is from ∼520 nm to longer than 700 nm, i.e.…”
Section: No From the Photometric Measurementsmentioning
confidence: 99%
“…However, because of the chemistry involved in the production of the two species, the altitudes of emission are separated with the NO 2 continuum emission peaking some 5-10 km higher than the FeO. Evans et al (2010) restricted the observations to latitudes equatorward of 40 • where the NO 2 continuum emission is believed to be only a minor contributor and the FeO emission to be the major contributor to the nightglow continuum. At auroral latitudes it is more likely the opposite situation, with the NO 2 continuum emission as the major contributor.…”
Section: No From the Photometric Measurementsmentioning
confidence: 99%
“…Following the observations of Evans et al (2010), the residual GLO-1 spectrum in Fig. 2, Panel C, is expected to include a component arising from mesospheric chemiluminescent FeO * emissions.…”
Section: Night Airglow Continuum Observations With the Glo-1 Spectrogmentioning
confidence: 99%
“…2, Panel C, is expected to include a component arising from mesospheric chemiluminescent FeO * emissions. Evans et al (2010) built their analysis on the observation of FeO * in persistent meteor trains by Jenniskens et al (2000). The FeO * component must be removed from the total residual continuum to isolate any previously unidentified features.…”
Section: Night Airglow Continuum Observations With the Glo-1 Spectrogmentioning
confidence: 99%
See 1 more Smart Citation